Penentuan Tipe Pasang Surut Perairan Pada alur Pelayaran Manokwari Denganmenggunakan Metode Admiralty - Suhaemi Suhaemi; Syafrudin Raharjo; Marhan Marhan (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2018)
Tidal waters are very important for port interests, sea transportation, fisheries industry, coastal engineering and coastal area mitigation. Tidal height formed is a superposition of tidal amplitude due to the gravitational pull of the sun, moon and earth. The Tidal components are K1, O1, P1, S2, M2, K2, M4, MS4. This study aims to determine the components and types of tides in the shipping channel of Manokwari-West Papua using the admiralty method. Formzahl 0.732 number means the type of tidal that is formed is mixed tide prevailing semidiurnal, two high and low tide, two high and one low tide or two times low tide one high tide in a day. Mean Sea Level (MSL) was caused by water conditions, coastlines and bathymetry, the gravitational forces of the moon and sun. The MSL was obtained 98 cm. large tidal range occurs during full moon conditions and low tides occur during perbani (1.62-2.44 m). The amplitude Mean High Water Level level reaches 279 cm and Mean Low Water Level reaches -83 cm.